Direct Clipping for Active Colonic Diverticular Bleeding Using an Endoclip with Re-grasping Function - Kishino, Takaaki; Yamakawa, Maiko (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Kishino T, Yamakawa M. Direct clipping for active colonic diverticular bleeding using an endoclip with re-grasping function. Turk J Gastroenterol. 2024;35(9):750-751.